2021
DOI: 10.1007/s12471-021-01545-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medical services evaluations for chest pain during first COVID-19 lockdown in Hollands-Midden, the Netherlands

Abstract: Objective To assess whether the COVID-19 lockdown in 2020 had negative indirect health effects, as people seem to have been reluctant to seek medical care. Methods All emergency medical services (EMS) transports for chest pain or out-of-hospital cardiac arrest (OHCA) in the Dutch region Hollands-Midden (population served > 800,000) were evaluated during the initial 6 weeks of the COVID-19 lockdown and during the same time period in 2019. The primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Ten studies reported or provided sufficient data to calculate the annual OHCA incidence (per 100,000 population) (Additional file 1 : Table S2) [ 6 8 , 26 , 31 , 32 , 35 37 , 39 ]. Among them, de Koning et al [ 35 ] reported the lowest annual OHCA incidence of 51 and 63 cases per 100,000 population in the pre-COVID-19 and COVID-19 time periods, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies reported or provided sufficient data to calculate the annual OHCA incidence (per 100,000 population) (Additional file 1 : Table S2) [ 6 8 , 26 , 31 , 32 , 35 37 , 39 ]. Among them, de Koning et al [ 35 ] reported the lowest annual OHCA incidence of 51 and 63 cases per 100,000 population in the pre-COVID-19 and COVID-19 time periods, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported or provided sufficient data to calculate the annual OHCA incidence (per 100,000 population) (Additional file 1 : Table S2) [ 6 8 , 26 , 31 , 32 , 35 37 , 39 ]. Among them, de Koning et al [ 35 ] reported the lowest annual OHCA incidence of 51 and 63 cases per 100,000 population in the pre-COVID-19 and COVID-19 time periods, respectively. Meanwhile, Glober et al [ 36 ] reported the highest annual OHCA incidence of 183 and 214 cases per 100,000 population in the pre-COVID-19 and COVID-19 time periods, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies provided data for the characteristic of shockable rhythm. [6][7][8][23][24][25]27,28,[31][32][33]35,36,38,39 The percentage who had shockable rhythm ranged from 3.6-40% across intervals of the pre-COVID-19 and COVID-19 time periods. Apart from Semeraro et al 31 , all studies reported a trend of lower percentage with shockable rhythm in the COVID-19 period as compared to the pre-COVID-19 period.…”
Section: Shockable Rhythmmentioning
confidence: 99%
“…* EMS, Emergency Medical Services; † UK, United Kingdom; ‡ USA, United States of America; § NR, Not Reported; || COVID-19, coronavirus disease 2019; # Study designs for all included studies were multicentred and retrospective in nature * EMS, Emergency Medical Services; † UK, United Kingdom; ‡ USA, United States of America; § NR, Not Reported; || COVID-19, coronavirus disease 2019; # Study designs for all included studies were multicentred and retrospective in nature * EMS, Emergency Medical Services; † UK, United Kingdom; ‡ USA, United States of America; § NR, Not Reported; || COVID-19, coronavirus disease 2019; # Study designs for all included studies were multicentred and retrospective in nature * EMS, Emergency Medical Services; † UK, United Kingdom; ‡ USA, United States of America; § NR, Not Reported; || COVID-19, coronavirus disease 2019; # Study designs for all included studies were multicentred and retrospective in nature * ROSC, Return of Spontaneous Circulation; † CI, Con dence Interval; ‡ OR, Odds Ratio; § N/A, Not Applicable; || OHCA, Out-of-Hospital Cardiac Arrest; # P values were obtained from two-proportions ztests comparing Pre-COVID-19 and COVID-19 pooled valuesAll studies achieved a score ranging from 7 to 9 on the Newcastle-Ottawa Scale, signifying high quality and low risk of bias for selection (Supplemental Table1).3.2.1 Primary Outcomes: Annual OHCA IncidenceTen studies reported or provided su cient data to calculate the annual OHCA incidence (per 100000 population) (Supplemental Table2).6-8, 24,29,30, 33-35,37 Among them, de Koning et al33 reported the lowest annual OHCA incidence of 51 and 63 cases per 100000 population in the pre-COVID-19 and COVID-19 time periods respectively. Meanwhile, Glober et al 34 reported the highest annual OHCA incidence of 183 and 214 cases per 100000 population in the pre-COVID-19 and COVID-19 time periods respectively.…”
mentioning
confidence: 99%
“…Overall survival was also lower, primarily in communities with moderate or high COVID-19 mortality [11]. Contrary to most of the publications in the Netherlands during the first COVID-19 lockdown, the incidence of OHCA remained on the sable level, while there was a significant reduction in the number of patients with chest pain or STEMI [12]. A Spanish Nationwide Prospective Cohort Study showed that during the COVID-19 period, the incidence of resuscitation attempts declined and survival to hospital admission (OR = 1.72; 95%CI = 1.46-2.04; p < 0.001) and discharge (OR = 1.38; 95%CI = 1.07-1.78; p = 0.013) fell compared to the non-COVID period.…”
mentioning
confidence: 67%